Temporal Association Between Ischemic Muscle Perfusion Recovery and the Restoration of Muscle Contractile Function After Hindlimb Ischemia - Goldberg, Emma J.; Schmidt, Cameron A.; Green, T. D.; Karnekar, R.; Yamaguchi, D. J.; Spangenberg, E. E.; McClung, Joseph M. (Frontiers in Physiology, 2019)
During incomplete skeletal muscle recovery from ischemia, such as that occurs with critical limb ischemia, the temporal relationship between recovery of muscle capillary perfusion and contractile function is poorly defined. We examined this relationship in BALB/cJ mice (N = 24) following unilateral hindlimb ischemia (HLI), which pre-clinically mimics the myopathy observed in critical limb ischemia patients. Specifically, we examined this relationship in two phenotypically distinct muscles (i.e., “oxidative” soleus – Sol and “glycolytic” extensor digitorum longus – EDL) 14- or 56-days after HLI. Although overall limb blood flow (LDPI) reached its’ recovery peak (48% of control) by HLI d14, the capillary networks in both the Sol and EDL (whole mount confocal imaging) were disrupted and competent muscle capillary perfusion (perfused lectin+μm2/muscle μm2) remained reduced. Interestingly, both Sol and EDL muscles recovered their distinct capillary structures and perfusion (Con Sol; 0.056 ± 0.02 lectin+μm2/muscle μm2, and Con EDL; 0.039 ± 0.005 lectin+μm2/muscle μm2) by HLI d56 (Sol; 0.062 ± 0.011 lectin+μm2/muscle μm2 and EDL; 0.0035 ± 0.005 lectin+μm2/muscle μm2), despite no further improvement in limb blood flow (LDPI). Both muscles suffered severe myopathy, indicated by loss of dystrophin positive immunostaining and the absence of stimulation induced isometric force production at HLI d14. Dystrophin immunofluorescence returned at HLI d56, although neither myofiber CSA (μm2) nor isometric force production (58 and 28% sustained deficits, Sol and EDL, respectively) recovered completely in either muscle. In summary, we reveal that the temporal relationship between the restoration of muscle capillary perfusion and functional ischemic skeletal muscle regeneration favors competent muscle capillary perfusion recovery in BALB/c mice in a phenotypically non-distinct manner.